Chemical Composition of High Organic Carbon Soil Amendments Affects Fertilizer-Derived N2O Emission and Nitrogen Immobilization in an Oxic Sandy Loam - Wei, Jing; Reichel, Rüdiger; Islam, Muhammad Saiful; Wissel, Holger; Amelung, Wulf; Brüggemann, Nicolas (Frontiers in Environmental Science, 2020)
Nitrous oxide (N2O) emission is a negative side effect of modern agriculture and a serious issue for global climate change. The combined application of nitrogen (N) fertilizer and high organic carbon soil amendments (HCA) has been regarded as an alternative to promote fertilizer-related N immobilization and enhance nitrogen use efficiency. The effect of HCA on N2O emission and N immobilization highly depends on its chemical composition, as it controls carbon (C) supply to soil microbes and reactivity of lignin-derived phenols to fertilizer-derived N species. Here we present a 127-d laboratory incubation study to explore the N2O emission and N immobilization after combined application of N fertilizer and HCA (wheat straw, spruce sawdust, and commercial alkali lignin) differing in their chemical composition. The 15N labelling technique was used to trace the transformation of fertilizer-N in ammonium (NH4+), NO3-, soil organic nitrogen (SON), and N2O. The amendment of wheat straw and spruce sawdust greatly promoted N immobilization and N2O emission, while lignin amendment enhanced the immobilization of fertilizer N. The chemical composition of HCA explained 26% of the total variance of fertilizer-derived N2O emission and N retention via soil microbial biomass, composition of lignin-derived phenols, and nitrification. The holocellulose/lignin ratio of HCA could be used as an indicator for predicting HCA decomposition, microbial N immobilization and N2O emission. In addition, the composition of lignin-derived phenols was affected by HCA amendment and significantly related to N2O emission and N retention. The varying chemical composition of HCA could thus be a promising tool for controlling N2O emission and N immobilization in environment-friendly and climate-smart agriculture.